Nitrogen cycling and functional gene diversity of drinking reservoir area in agricultural districts: Implications for nitrogen transformation processes - Mengze Li; Wenwen Wang; Shengwu Yuan; Kun Wang; Shuhang Wang; Wei Li; Xia Jiang; Wenqiang Zhang; Baoqing Shan (Ecological Indicators)
Nitrogen pollution in aquatic ecosystems, especially in shallow lakes and reservoirs, has intensified in recent years due to human activities like agricultural fertilization and wastewater discharge. However, the microbial mechanisms driving nitrogen cycling are not well understood. This study examines nitrogen migration, transformation, and the microbial mechanisms driving nitrogen cycling in the QuanMin Reservoir, which is heavily influenced by agricultural activities and land runoff. The reservoir serves as a model for understanding nitrogen pollution, and its effects on water quality. The results indicate that total nitrogen (TN) concentrations in the overlying water ranged from 0.43 to 2.22 mg/L, with nitrate nitrogen accounting for an average of 52 % of the total. Nitrogen cycling was mainly driven by key genes involved in assimilatory nitrate reduction to ammonium and denitrification, with notable differences in gene abundance between river and reservoir waters. Denitrification genes were dominant in the sediments, and reservoir sediments showed a higher potential for nitrogen fixation than river sediments. Additionally, nitrate concentrations were significantly higher in riverine waters, while TN and total carbon levels in sediments were notably lower in the reservoir compared to the river. These environmental parameters were closely associated with the abundance of nitrogen functional genes in water and sediment. These findings advance mechanistic understanding of microbial nitrogen cycling in anthropogenically impacted reservoirs. Nonetheless, the complexity and variability of nitrogen cycling in these reservoirs highlight the need for further targeted research to enhance understanding and improve management practices.